Sosialisasi Pencegahan Bullying Pada Siswa SMPN 3 Amarasi Selatan-Satap, Kabupaten Kupang - Algonsia Dwinda Maharani; Marselina Hadija Daiman; Indriyati indriyati; Hendrikus Likusina Kaha; Marianus Kleden (Universitas Negeri Gorontalo, 2025)
A bullying prevention outreach initiative was implemented at SMPN 3 Amarasi Selatan-Satap, located in Kupang Regency, in response to the ongoing issue of bullying that has not been systematically tackled. The need for this initiative was highlighted by initial observations revealing a lack of awareness among students regarding different forms of bullying, coupled with the report from five students who identified themselves as victims of physical bullying. The program involved 30 students from the seventh and eighth grades, utilizing lectures, discussions, and questionnaires. Evaluation results indicated a substantial increase in students' comprehension of bullying, rising from 20% to 93.33%. Although the revelation that five students had faced physical bullying should have been a main focus for developing additional interventions, it was not thoroughly examined during this event. Nevertheless, students showed great enthusiasm throughout the program. This initiative is anticipated to be a preliminary step towards fostering a safer school environment through continuous collaboration among the school, parents, and the community.